Masking of typical TLR4 and TLR5 ligands modulates inflammation and resolution by Helicobacter pylori - Suneesh Kumar, Pachathundikandi; Tegtmeyer-Backert, Nicole; Backert, Steffen (Trends in Microbiology, 2023)
Helicobacter pylori is a paradigm of chronic bacterial infection and is associated with peptic ulceration and malignancies. H. pylori uses specific masking mechanisms to avoid canonical ligands from activating Toll-like receptors (TLRs), such as lipopolysaccharide (LPS) modification and specific flagellin sequences that are not detected by TLR4 and TLR5, respectively. Thus, it was believed for a long time that H. pylori evades TLR recognition as a crucial strategy for immune escape and bacterial persistence. However, recent data indicate that multiple TLRs are activated by H. pylori and play a role in the pathology. Remarkably, H. pylori LPS, modified through changes in acylation and phosphorylation, is mainly sensed by other TLRs (TLR2 and TLR10) and induces both pro- and anti-inflammatory responses. In addition, two structural components of the cag pathogenicity island-encoded type IV secretion system (T4SS), CagL and CagY, were shown to contain TLR5-activating domains. These domains stimulate TLR5 and enhance immunity, while LPS-driven TLR10 signaling predominantly activates anti-inflammatory reactions. Here, we discuss the specific roles of these TLRs and masking mechanisms during infection. Masking of typical TLR ligands combined with evolutionary shifting to other TLRs is unique for H. pylori and has not yet been described for any other species in the bacterial kingdom. Finally, we highlight the unmasked T4SS-driven activation of TLR9 by H. pylori, which mainly triggers anti-inflammatory responses.
CRIS-Team Scopus Importer:2023-04-14
Keywords: H. pylori; inflammation; PAMP; PRR; T4SS; TLR